How is caring for grandchildren associated with grandparents’ health: the mediating effect of internet use - Wang, Jie; Gu, Rongxing; Zhang, Lanxi; Zhang, Li (Frontiers in Public Health, 2023)
Objective: Prior studies showed mixed results of the association between grandchild care and grandparents' health. This research focused on the mechanisms behind the above link by studying how internet use served as a mediator through which grandchild care has impacted grandparents' health. The study aimed to draw implications to improve health of grandparents who offer care to grandchildren.Methods: Using a sample of 16,829 grandparents aged 50 through 80 from the 2018 wave of China Health and Retirement Longitudinal Study (CHARLS), the study relied on the KHB method to conduct the analysis. Grandparental health was measured by self-rated health (SRH), instrumental activity of daily living (IADL), life satisfaction and depression.Results: Overall, grandchild care had a positive effect on grandparental health. Those who engaged in grandchild care were more likely to use internet. In addition, internet use mediated the ways in which grandchild care impacted grandparents' health. Interne use generally promoted the positive influence of grandparental caregiving on grandparents' health. Specifically, the mediating effects of watching videos and chatting through the internet were most pronounced among urban grandmothers. The mediating effects of watching news were most noticeable among both urban grandmothers and grandfathers.Internet use served as a mediator in the association between grandchild child care and grandparental health. Promoting internet usage may be an effective way reducing the negative impact of grandchild care on grandparents' mental health. It could also increase the positive effect of caregiving on grandparents' SRH and functional independence. The study also underscored the importance of taking rural-urban context and gender role into consideration when studying intergenerational caregiving and Chinese grandparents' health.